Hypertension Patients' Knowledge, Attitudes, and Control Measures in Bukittinggi: A Qualitative Study - Apriza, Cici; Djuwita, Ratna; Martha, Evi; Besral, Besral (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
Hypertension remains a major global health concern, causing numerous deaths worldwide. Approximately 1.13 billion people suffer from hypertension, with an estimated 10.44 million deaths annually due to hypertension and its complications. This study aims to explore the knowledge, attitudes, and actions taken by hypertensive patients in Bukittinggi City. The research was conducted in the Mandiangin Health Center Working Area, involving 17 hypertension patients, one officer responsible for the Non-Communicable Diseases (NCD) program, and the head of the community health center. This qualitative study used a phenomenological approach, identifying three main themes: knowledge, attitude, and action. The sub-themes include